BEAUTY STEREOTYPE PORTRAYED THROUGH CELIE'S PERFORMANCE IN "THE COLOR PURPLE" NOVEL BY ALICE WALKER - Annisa Harli Tanjung; Nenden Rikma Dewi (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
The stereotype is commonly used to recognize and identify particular individual or societies. One of stereotype which is depicted in Alice Walker’s “The Color Purple" is the beauty. The beauty stereotype is experienced by most of women in the story. They are required to fulfill certain standards in order to be labeled as a graceful and beautiful woman, even that standards are imposed to be decisive for the women to enter society and the society’s system. The existing system in the community is majority controlled by thought or ideology that emphasizes the male opinion, or it is also called patriarchy. Celie, an African-American woman, is a main character facing the oppression not only because she is uneducated but also unfit the stereotype. In order to recognize kinds of beauty stereotype, this paper is using descriptive analytic method. Meanwhile, Naomi Wolf (2002) ideas on Beauty Myth is used to identify the issue. Through finding and discussions, it can be concluded that body figure and style are two dominant parts in women’s beauty stereotype.